The Performance Evaluation of Catfish Hatchery Business in Maguan Village, Ngajum Subdistrict, Malang Regency, East Java - Nina Widyawati; Anthon Efani; Tiwi Nurjannati Utami (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
The aims of the research are to know and to analyze the performance of catfish hatchery business in Desa Maguan viewed from the perspective of finance and non finance. The research use survey method with qualitative and quantitative descriptive research. The result show that the business performance is 77,44% in "very healthy" condition with A category. The business in financial perspective has very good performance with AA category with score 93,75. The strategy in financial perspective are they need to increase net profit with productive investment (adding pond) and to minimize costs. From the perspective of customers, this business has a poor performance compared to other perspectives with the BBB category with a score of 56.25%. The strategy in customer perspective is they need to enhance customer satisfaction which can be obtained by looking ahead of product, price, promotion, and place. On the internal business perspective, the business has a pretty good performance with A category with a score of 70%. The strategy in internal business perspective are they should be keeping quality standards on fish fry, adding new pond, and giving aftersales service. In the learning and growth perspective has a very good performance with the category of AA with a score of 91.7%. The strategy should be achieved to maintain and to improve learning and growth perspective is improvement of employee’s satisfaction by giving bonus and accompany employees while they are working. Keywords: evaluation, performance, catfish hatchery business, Balanced Score Card